A zinc oxide sunscreen material based on monodisperse silicon microsphere modification and preparation method thereof

By solving the problem of poor skin sensation in sunscreen products by pushing zinc oxide loads on the carboxyl carboxyl group with negatively charged active groups, and realizing the dual improvement of sunscreen performance and skin sensation.

CN118873422BActive Publication Date: 2025-01-28GUANGDONG PHARMA UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411346134.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-28
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Zinc oxide has poor skin feeling in sunscreen products, including poor smoothness, large amount of use, heavy product, uneven particle distribution, and difficult to apply evenly, affecting the sunscreen effect.

Method used

By using the silicon -sized silicon microspheres with negatively charged active group carboxyls with negatively charged active groups on the surface. Zinc sunscreen material.

Benefits of technology

The improvement of sun protection performance is realized, and the skin feel is improved, the products are lighter and breathable, and the thickness and stickiness of traditional zinc oxide products are avoided, and the user experience is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118873422B_ABST
    Figure CN118873422B_ABST
Patent Text Reader

Abstract

The invention discloses a zinc oxide sunscreen material modified by monodisperse silicon microspheres and a preparation method thereof. The zinc oxide sunscreen material modified by monodisperse silicon microspheres comprises silicon dioxide microspheres and zinc oxide loaded on the surface of the silicon dioxide microspheres. The preparation method comprises: S1. providing silicon dioxide microspheres with negatively charged active groups carboxyl distributed on the surface; S2. depositing positively charged zinc ions on the surface of the silicon dioxide microspheres in step S1 to form zinc hydroxide under an alkaline environment, and obtaining the zinc oxide sunscreen material modified by monodisperse silicon microspheres through heat treatment. Compared with the prior art, the invention can avoid the problems of poor skin feel of zinc oxide sunscreen materials, and has the advantages of good sunscreen, good skin feel, and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetics, and in particular to a zinc oxide sunscreen material based on monodisperse silicon microsphere modification and a preparation method thereof. Background Art

[0002] Zinc oxide (ZnO) is an inorganic substance widely used in sunscreen products and is known for its excellent sunscreen performance. As a natural mineral, zinc oxide can effectively absorb, scatter and reflect ultraviolet (UV) radiation, covering the UVA (320-400nm) and UVB (280-320nm) bands. This full-band protection capability makes zinc oxide highly respected in the sunscreen field, especially in products that require long-lasting broad-spectrum protection. Zinc oxide is widely used in various sunscreen products, including creams, lotions, sprays, foundations, etc.

[0003] Although zinc oxide performs well in the field of sun protection, it has certain defects in skin feel in actual use: first, because pure zinc oxide crystals belong to the angular cubic crystal system, the smoothness of its powder is poor; second, the amount of traditional zinc oxide powder in the product often needs to be added to more than 10wt% to achieve the ideal sun protection effect, which leads to a large amount of oil in the product and a heavy surface; third, traditional zinc oxide particles are relatively large and easily form thick white marks on the skin surface, making users feel sticky or stuffy. These defects seriously affect the user experience, especially when it is necessary to spend a long time outdoors or use it in a high temperature environment. In addition, the uneven distribution of zinc oxide particles will also make it difficult to apply the product evenly, thus affecting the sun protection effect.

[0004] In view of this, it is urgent to solve the defects of zinc oxide in the sun protection field, such as poor skin feel. Summary of the invention

[0005] The purpose of the present invention is to provide a zinc oxide sunscreen material based on monodisperse silicon microspheres and a preparation method thereof, in view of the above-mentioned deficiencies in the prior art, which can avoid the defects of zinc oxide such as poor skin feel and has the advantages of good sun protection and good skin feel.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] In a first aspect, a zinc oxide sunscreen material based on monodisperse silicon microspheres modified by the present invention comprises silicon dioxide microspheres and zinc oxide loaded on the surface of the silicon dioxide microspheres, and a preparation method comprises:

[0008] S1. providing silica microspheres having negatively charged active groups carboxyl groups distributed on the surface;

[0009] S2. In an alkaline environment, positively charged zinc ions are deposited on the surface of the silica microspheres in step S1 to form zinc hydroxide, thereby obtaining silica microspheres loaded with zinc hydroxide; and a zinc oxide sunscreen material modified based on monodisperse silica microspheres is obtained by heat treatment.

[0010] Preferably, the mass ratio of the silica microspheres to the zinc oxide loaded on the surface of the silica microspheres is 400-600; the polymer dispersibility index (PDI) of the silica microspheres is 0.041-0.288; and the polymer dispersibility index (PDI) of the silica microspheres loaded with zinc hydroxide is 0.069-0.181.

[0011] Preferably, the particle size range of the zinc oxide sunscreen material based on the modification of monodisperse silica microspheres is 1220-1300 nm; and the potential range of the zinc oxide sunscreen material based on the modification of monodisperse silica microspheres is -42.6 to -41.2 mV.

[0012] In a second aspect, a method for preparing the aforementioned zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to the present invention comprises the following steps:

[0013] S1. providing silica microspheres having negatively charged active groups carboxyl groups distributed on the surface;

[0014] S2. In an alkaline environment, positively charged zinc ions are deposited on the surface of the silica microspheres in step S1 to form zinc hydroxide, and a zinc oxide sunscreen material modified based on monodisperse silica microspheres is obtained by heat treatment.

[0015] Preferably, the step S1 comprises:

[0016] S1.1 provides a solution C containing citric acid;

[0017] S1.2 provides a ethyl orthosilicate solution D;

[0018] S1.3 Add tetraethyl orthosilicate solution D dropwise into solution C containing citric acid to fully react to obtain suspension E. After suction filtration and washing, silica microspheres with negatively charged active groups carboxyl distributed on the surface are obtained.

[0019] Preferably, the step S1.1 further comprises:

[0020] S1.1.1 Dissolve citric acid in anhydrous ethanol and stir to fully dissolve it to obtain solution A;

[0021] S1.1.2 Dilute solution A with an appropriate amount of pure water to obtain solution B;

[0022] S1.1.3 Dissolve ammonia water in solution B and stir to fully dissolve it to obtain solution C containing citric acid;

[0023] Preferably, the amount of citric acid added to the solution A is 0.1-0.5 g, and the amount of anhydrous ethanol added is 100 mL; the amount of pure water added to the solution B is 30 mL; the concentration of ammonia water in the citric acid-containing solution C is 25 wt%, and the amount added is 2-15 mL.

[0024] Preferably, the step S1.2 further comprises: S1.2.1 dissolving tetraethyl orthosilicate in anhydrous ethanol and dissolving it fully by ultrasonication to obtain a tetraethyl orthosilicate solution D; the amount of tetraethyl orthosilicate added in the tetraethyl orthosilicate solution D is 4-15 mL, and the amount of anhydrous ethanol added is 10-30 mL.

[0025] Preferably, the sufficient reaction time in the step S1.3 is 8 to 12 hours; in the step S1.3, washing is performed with pure water and anhydrous ethanol in sequence; washing is performed twice with 100 mL of pure water and once with 100 mL of anhydrous ethanol.

[0026] Preferably, the step S2 further comprises:

[0027] S2.1 Add zinc acetate solution dropwise into silica microsphere suspension G to fully react to obtain suspension H;

[0028] S2.2 Add sodium hydroxide solution dropwise into suspension H to fully react to obtain suspension I;

[0029] S2.3 The suspension I is filtered, washed, dried and calcined to obtain a zinc oxide sunscreen material modified with monodisperse silicon microspheres.

[0030] Preferably, the step S2.1 further comprises:

[0031] S2.1.1 Disperse the silica microspheres prepared in step S1 in anhydrous ethanol to obtain a suspension F;

[0032] S2.1.2 dissolving ammonia water in suspension F to obtain silica microsphere suspension G;

[0033] In step S2.1.1, the amount of silica microspheres added was 5 g, and the amount of anhydrous ethanol added was 40 mL;

[0034] In step S2.1.2, the concentration of ammonia water is 25wt%, and the amount added is 1mL;

[0035] The concentration of the zinc acetate solution is 5 mmol / L, and the addition amount is 0.05-0.20 mL;

[0036] Preferably, the concentration of the sodium hydroxide solution in step S2.2 is 1 mmol / L, and the amount added is 1 mL;

[0037] Preferably, the step S2.3 further comprises:

[0038] S2.3.1 Filter the suspension I, wash it with pure water and anhydrous ethanol in turn, and dry it to obtain powder J;

[0039] Step S2.3.1: Wash twice with 100 mL of pure water, once with 100 mL of anhydrous ethanol, and dry at 55 °C.

[0040] Preferably, the reaction time of step S2.1 is 0.5-1.5 h; the reaction time of step S2.2 is 0.5-1.0 h; and the calcination temperature of step S2.3 is 200° C. and the time is 2 h.

[0041] The invention firstly uses citric acid (CA), ammonia water (NH3·H2O) and tetraethyl orthosilicate (TEOS) as raw materials, successfully prepares monodisperse silica microspheres (SNS_Ci) with high surface charge at room temperature, and prepares the silica microspheres through chemical reaction. Since the hydroxyl groups in the citric acid molecules can participate in the hydrolysis reaction of tetraethyl orthosilicate (TEOS), the prepared silica microspheres have high surface charge due to the introduction of highly active functional group carboxyl groups, and have excellent monodispersity due to the repulsion of the same charges. Meanwhile, in the process of preparing the silica microspheres, the citric acid and ammonia water in the solution form a buffer pair, so that the pH value of the solution is more easily maintained in a range that is conducive to the generation of the silica microspheres.

[0042] Subsequently, zinc hydroxide is loaded on the surface of silica microspheres under alkaline conditions, and the negatively charged active group carboxyl introduced on the surface of silica microspheres forms a specific interaction force (including electrostatic interaction and complexation) with the subsequently added positively charged zinc ions, so that active sites are formed on the surface of silica microspheres. By adjusting the appropriate alkaline environment, in-situ secondary deposition occurs on the surface of silica microspheres to generate zinc hydroxide (Zn(OH)2), which is relatively evenly loaded on the surface of silica microspheres. The study found that when the amount of zinc acetate solution used in the synthesis process is relatively small (i.e., the amount added is not more than 0.2 mL), based on the interaction between zinc ions and negative ions on the surface of silica microspheres, zinc ions are alkaline hydrolyzed and loaded on the surface of silica microspheres in the form of a new phase, so that the final sunscreen material has better sunscreen performance.

[0043] After the above steps, the obtained silica microspheres loaded with zinc hydroxide also have excellent monodispersity. Monodispersity plays a vital role in the preparation of various nanomaterials and composite materials. Monodispersity refers to the uniform particle size and high consistency, which has many advantages for loading zinc oxide (ZnO) on the surface of silica microspheres. The silica microspheres loaded with zinc hydroxide obtained in the present invention have a monodispersity PDI value of 0.069~0.181. The smaller the PDI value, the better the corresponding monodispersity, and the more uniform the particle size of the sample, so that the final sunscreen material has the advantages of uniformly loaded zinc oxide distribution, excellent optical properties, good protective effect, improved skin feel, high physical and chemical stability, easy processing and large-scale application, etc., and better user experience:

[0044] 1) Monodisperse silica microspheres have a consistent surface area and morphology, allowing zinc oxide to be evenly distributed on the surface of the microspheres. This uniform loading distribution helps achieve uniform sun protection and avoids the problem of insufficient protection in certain areas of the sunscreen product.

[0045] 2) The monodispersity of silica microspheres can effectively reduce light scattering and aggregation between particles, thereby improving the optical transparency of the material. This not only helps to maintain the transparency and aesthetics of sunscreen products, but also improves the optical properties of zinc oxide, making it more efficient in absorbing and scattering ultraviolet rays.

[0046] 3) Since the monodisperse silica microspheres can achieve uniform distribution of zinc oxide, the overall protection effect of sunscreen products is more uniform and reliable, effectively improving the product's sun protection factor (SPF) and broad-spectrum protection (UVA and UVB).

[0047] 4) Monodispersed silica microspheres have good fluidity and dispersibility, and can provide a silkier and lighter skin feel during the application process. Zinc oxide is evenly distributed on the carrier and is not easy to form a granular or heavy feeling, thereby improving the skin feel defects of traditional zinc oxide sunscreen products.

[0048] 5) Monodisperse silica microspheres can provide a more stable structure, reduce the interaction force between microspheres, and reduce the risk of agglomeration. For zinc oxide particles loaded on their surface, they can significantly improve the physical stability of the composite material and ensure its long-term effectiveness and stability during use.

[0049] 6) The chemical inertness and good monodispersity of silica microspheres can provide a stable loading platform, reduce the direct contact between zinc oxide and the external environment (such as air, moisture, and other chemical components), thereby enhancing the chemical stability of zinc oxide and extending the service life of the product.

[0050] 7) Silica microspheres with good monodispersity show better controllability and repeatability during processing and preparation, which is conducive to large-scale production and application.

[0051] Finally, after heat treatment, i.e. calcination, zinc oxide is loaded on the surface of silica microspheres to obtain a zinc oxide composite sunscreen material (SNS_Ci@ZnO) modified based on silica microspheres, which has better sunscreen performance.

[0052] The present invention significantly improves the skin feel of the final sunscreen product by loading zinc oxide on the surface of silica microspheres, making it lighter and more breathable, and leaving no obvious marks on the skin. The sunscreen material retains the excellent sunscreen performance of zinc oxide and greatly improves the user experience.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The present invention uses silicon dioxide microspheres as carriers to load zinc oxide materials to obtain a zinc oxide sunscreen material (SNS_Ci@ZnO) modified based on monodisperse silicon microspheres, which has the advantages of strong sun protection, physicochemical stability, good dispersibility, good biocompatibility, and little environmental harm. In addition, the preparation method has the advantages of simple operation, low cost, and green environmental protection.

[0055] The above is an overview of the technical solution of the invention. The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The SEM images of the silica microspheres SNS_Ci and the sunscreen material SNS_Ci@ZnO in the present invention;

[0057] Figure 2 FT-IR spectra of the silica microspheres SNS without citric acid modification, the silica microspheres SNS_Ci modified with citric acid, and the sunscreen material SNS_Ci@ZnO in the present invention;

[0058] Figure 3 This is the EDS spectrum of the sunscreen material SNS_Ci@ZnO in the present invention;

[0059] Figure 4 XRD spectra of the silica microspheres SNS without citric acid modification, the silica microspheres SNS_Ci modified with citric acid, and the sunscreen material SNS_Ci@ZnO in the present invention;

[0060] Figure 5 TEM image of the sunscreen material SNS_Ci@ZnO in the present invention;

[0061] Figure 6 UV spectra of zinc oxide ZnO, silicon dioxide microspheres SNS_Ci and sunscreen material SNS_Ci@ZnO in the present invention;

[0062] Figure 7 UV spectra of the sunscreen material SNS_Ci@ZnO with different zinc acetate addition amounts in the present invention (unit: mL). DETAILED DESCRIPTION

[0063] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following is a detailed description in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0064] The steps implemented by the present invention are mainly divided into two steps:

[0065] The first step is to prepare silica microspheres SNS_Ci, using citric acid (CA), ammonia (NH3·H2O) and tetraethyl orthosilicate (TEOS) as raw materials. During the synthesis process, ammonia provides an alkaline environment, making the process of TEOS hydrolysis to generate silica controllable, and obtaining silica microspheres (SNS_Ci) with moderate particle size. The second step is to prepare the sunscreen material SNS_Ci@ZnO. Using the active groups such as hydroxyl and carboxyl on the surface of silica microspheres (SNS_Ci), under certain alkaline conditions, zinc ions combine with the active groups on the surface of the microspheres and react to generate zinc hydroxide (Zn(OH)2), which is relatively uniformly loaded on the surface of the silica microspheres. After heat treatment such as calcination, a zinc oxide sunscreen material (SNS_Ci@ZnO) modified based on monodisperse silica microspheres is prepared.

[0066] In order to characterize the prepared sunscreen material SNS_Ci@ZnO of the present invention, the prepared sunscreen material SNS_Ci@ZnO was prepared into a suspension of appropriate concentration, and the sunscreen properties were measured by ultraviolet spectrophotometer. In addition, the particle size, PDI and potential of the samples in the examples were measured using a Malvern laser particle size analyzer, and the particle size was the average particle size in the wet state.

[0067] The first aspect of the present invention provides a zinc oxide sunscreen material modified based on monodisperse silicon microspheres, the zinc oxide sunscreen material modified based on monodisperse silicon microspheres comprises silicon dioxide microspheres and zinc oxide loaded on the surface of the silicon dioxide microspheres, and the preparation method comprises:

[0068] S1. Providing silica microspheres (SNS_Ci) with negatively charged active groups carboxyl distributed on the surface;

[0069] S2. In an alkaline environment, positively charged zinc ions are deposited on the surface of the silica microspheres in step S1 to form zinc hydroxide, thereby obtaining silica microspheres loaded with zinc hydroxide; and a zinc oxide sunscreen material (SNS_Ci@ZnO) modified based on monodisperse silica microspheres is obtained through heat treatment.

[0070] Preferably, the mass ratio of the silica microspheres to the zinc oxide loaded on the surface of the silica microspheres is 400-600; and / or the polymer dispersibility index (PDI) of the silica microspheres loaded with zinc hydroxide is 0.069-0.181.

[0071] Preferably, the particle size range of the zinc oxide sunscreen material based on the modification of monodisperse silica microspheres is 1220-1300 nm; and / or, the potential range of the zinc oxide sunscreen material based on the modification of monodisperse silica microspheres is -42.6 to -41.2 mV.

[0072] The second aspect of the present invention provides a method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres, and the specific implementation process includes:

[0073] First, the silica microspheres SNS_Ci are prepared, including the following specific steps:

[0074] 1) Dissolve citric acid in anhydrous ethanol and stir to fully dissolve it to obtain solution A;

[0075] 2) Dilute solution A with pure water to obtain solution B;

[0076] 3) Dissolve ammonia water in solution B and stir to fully dissolve it to obtain solution C containing citric acid;

[0077] 4) dissolving ethyl orthosilicate in anhydrous ethanol and dissolving it fully by ultrasonication to obtain ethyl orthosilicate solution D;

[0078] 5) Add the ethyl orthosilicate solution D dropwise into the solution C containing citric acid, and react for a certain period of time under sufficient stirring to obtain a suspension E;

[0079] 6) The suspension E is filtered and washed with pure water and anhydrous ethanol in sequence to obtain silica microspheres SNS_Ci;

[0080] Preferably, in step 1), the amount of citric acid added to solution A is 0.1-0.5 g, and the amount of anhydrous ethanol added is 100 mL;

[0081] Preferably, the amount of pure water added to solution B in step 2) is 30 mL;

[0082] Preferably, the concentration of ammonia water in the solution C containing citric acid in step 3) is 25wt%, and the amount added is 2-15mL;

[0083] Preferably, in step 4), the amount of ethyl orthosilicate added to the ethyl orthosilicate solution D is 4-15 mL, and the amount of anhydrous ethanol added is 10-30 mL;

[0084] Preferably, the reaction time in step 5) is 8 to 12 hours;

[0085] Preferably, in step 6), 100 mL of pure water is used for washing twice, and 100 mL of anhydrous ethanol is used for washing once.

[0086] Secondly, the preparation of zinc oxide sunscreen material SNS_Ci@ZnO based on monodisperse silicon microspheres modification includes the following specific steps:

[0087] Disperse the silica microspheres SNS_Ci in anhydrous ethanol and stir to fully disperse them to obtain a suspension F;

[0088] Dissolve ammonia water in suspension F to obtain suspension G;

[0089] A certain amount of zinc acetate solution with a certain concentration is added dropwise to the suspension G, and the suspension is reacted for a certain period of time under sufficient stirring to obtain a suspension H;

[0090] A certain amount of sodium hydroxide solution with a certain concentration is added dropwise to the suspension H, and the suspension is reacted for a certain period of time under sufficient stirring to obtain a suspension I;

[0091] The suspension I was filtered, washed with pure water and anhydrous ethanol in turn, and then dried to obtain powder J;

[0092] The powder J was calcined in a tube furnace to obtain the zinc oxide sunscreen material SNS_Ci@ZnO based on monodisperse silicon microspheres;

[0093] Preferably, in step 1), the amount of SNS_Ci added is 5 g, and the amount of anhydrous ethanol added is 40 mL;

[0094] Preferably, the concentration of ammonia water in step 2) is 25wt%, and the amount added is 1mL;

[0095] Preferably, in step 3), the concentration of the zinc acetate solution is 5 mmol / L, the amount added is 0.05-0.2 mL, and the reaction time is 0.5-1.5 h;

[0096] Preferably, in step 4), the concentration of the sodium hydroxide solution is 1 mmol / L, the amount added is 1 mL, and the reaction time is 0.5-1.0 h;

[0097] Preferably, in step 5), the sample is washed twice with 100 mL of pure water, washed once with 100 mL of anhydrous ethanol, and dried at 55°C.

[0098] Preferably, the calcination temperature in step 6) is 200° C. and the calcination time is 2 h.

[0099] Example 1: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci, and the specific steps are as follows:

[0100] 1) Dissolve 0.5 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A;

[0101] 2) Dilute solution A with 30 mL of pure water to obtain mixed solution B;

[0102] 3) Dissolve 10 mL of aqueous ammonia (the concentration of aqueous ammonia is 25 wt%) in solution B to obtain solution C;

[0103] 4) Dissolve 10 mL of ethyl orthosilicate in 10 mL of anhydrous ethanol to obtain solution D;

[0104] 5) Add solution D dropwise into solution C and react for 8 hours to obtain suspension E;

[0105] 6) Suspension E was filtered and washed twice with 100 mL of pure water and once with 100 mL of anhydrous ethanol to obtain silica microspheres, which were labeled as SNS_Ci-1 (abbreviated as SNS_Ci) and stored for future use.

[0106] Example 2: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci. Referring to Example 1, only the amount of citric acid is changed to obtain silica microspheres, which are marked as SNS_Ci-2. The specific steps are as follows:

[0107] 1) Dissolve 0.2 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A.

[0108] Example 3: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci. Referring to Example 1, only the amount of citric acid is changed to obtain silica microspheres, which are marked as SNS_Ci-3. The specific steps are as follows:

[0109] 1) Dissolve 0.3 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A.

[0110] Example 4: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci. Referring to Example 1, only the amount of citric acid is changed to obtain silica microspheres, which are marked as SNS_Ci-4. The specific steps are as follows:

[0111] 1) Dissolve 0.4 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A.

[0112] Example 5: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci. Referring to Example 1, only the amount of citric acid is changed to obtain silica microspheres, which are marked as SNS_Ci-5. The specific steps are as follows:

[0113] Solution A was obtained by dissolving 0.1 g of citric acid in 30 mL of pure water.

[0114] Example 6: This example provides a method for preparing silica microspheres SNS_Ci and silica microspheres SNS_Ci. Referring to Example 1, only the amount of citric acid is changed to obtain silica microspheres, which are marked as SNS_Ci-6. The specific steps are as follows:

[0115] 1) Dissolve 0.6 g of citric acid in 100 mL of anhydrous ethanol to obtain solution A.

[0116] Example 7: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof, comprising the following specific steps:

[0117] 1) Dispersing 5 g of silica microspheres SNS_Ci-1 (prepared in Example 1) in 40 mL of anhydrous ethanol to obtain a suspension F;

[0118] 2) Add 1 mL of aqueous ammonia (the concentration of aqueous ammonia is 25 wt%) to suspension F to obtain suspension G;

[0119] 3) Add 0.2 mL of zinc acetate solution (the concentration of zinc acetate solution is 5 mmol / L) dropwise into suspension G, and react for 1 h under sufficient stirring to obtain suspension H;

[0120] 4) 1 mL of sodium hydroxide solution (the concentration of the sodium hydroxide solution is 1 mmol / L) was added dropwise to the suspension H, and the mixture was stirred for 30 min to obtain a suspension I;

[0121] 5) The suspension I was filtered and washed twice with 100 mL of pure water and once with 100 mL of anhydrous ethanol. After washing, it was dried at 55°C to obtain powder J;

[0122] 6) The powder J was calcined in a tubular furnace at a temperature of 200°C for 2 hours to obtain a zinc oxide sunscreen material based on monodisperse silicon microspheres, which was labeled as SNS_Ci@ZnO-1 (abbreviated as SNS_Ci@ZnO) and stored for future use.

[0123] Example 8: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-2. The specific steps are as follows:

[0124] 3) Add 0.4 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0125] Example 9: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-3. The specific steps are as follows:

[0126] 3) Add 0.6 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0127] Example 10: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-4. The specific steps are as follows:

[0128] 3) Add 0.8 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0129] Example 11: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-5. The specific steps are as follows:

[0130] 3) Add 1 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0131] Example 12: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-6. The specific steps are as follows:

[0132] 3) Add 0.05 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0133] Example 13: This example provides a zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silicon microspheres and a preparation method thereof. Referring to Example 7, only the volume of the zinc acetate solution is changed to obtain a zinc oxide sunscreen material modified by monodisperse silicon microspheres, which is marked as SNS_Ci@ZnO-7. The specific steps are as follows:

[0134] 3) Add 0.1 mL of zinc acetate solution (the concentration of zinc acetate is 5 mmol / L) dropwise into suspension G, and react for 1 h with sufficient stirring to obtain suspension H.

[0135] In order to further characterize the silica microspheres SNS_Ci and the zinc oxide sunscreen material SNS_Ci@ZnO modified by monodisperse silica microspheres of the present invention, tests were performed and the test results are shown in Table 1 below:

[0136] Table 1 Test results of Examples 1 to 13

[0137]

[0138] Combined with Figures 1 to 7 The analysis is as follows:

[0139] Depend on Figure 1 From the SEM images of silica microspheres SNS_Ci and sunscreen material SNS_Ci@ZnO, it can be seen that both silica microspheres SNS_Ci and sunscreen material SNS_Ci@ZnO are spherical under microscopic observation, with a diameter of about 1000nm. Compared with silica microspheres SNS_Ci, the morphology of sunscreen material SNS_Ci@ZnO has not changed significantly, indicating that the sunscreen material has the same excellent skin feel as SNS_Ci.

[0140] Depend on Figure 2 The FT-IR spectra of the silica microspheres SNS without citric acid modification, the silica microspheres SNS_Ci modified with citric acid, and the sunscreen material SNS_Ci@ZnO show that the 552 cm -1 、529cm -1 The absorption peak at is caused by the stretching vibration of the Zn-O bond, indicating that zinc oxide is successfully loaded on the surface of the silica microspheres SNS_Ci, and the sunscreen material SNS_Ci@ZnO is successfully prepared containing Zn-O bonds.

[0141] Depend on Figure 3From the EDS spectrum of the sunscreen material SNS_Ci@ZnO, it can be seen that the sunscreen material SNS_Ci@ZnO contains a certain amount of zinc (Zn) element, indicating that zinc oxide is successfully loaded on the surface of the silica microspheres SNS_Ci, which corresponds to the FT-IR graph.

[0142] Figure 4 In the XRD patterns of silica microspheres SNS without citric acid modification, silica microspheres SNS_Ci with citric acid modification, and sunscreen material SNS_Ci@ZnO, the blue line color is the sunscreen material SNS_Ci@ZnO, the red line color is the silica microspheres SNS_Ci with citric acid modification, the black line color is the unmodified silica microspheres SNS, and the standard card of traditional zinc oxide is shown below. In the XRD pattern of the sunscreen material SNS_Ci@ZnO, no specific lattice peak corresponding to the traditional zinc oxide powder can be found, indicating that when the appropriate amount of zinc salt is controlled during synthesis, when secondary deposition occurs on the surface of the silica microspheres, zinc oxide is loaded on the surface of the silica microspheres SNS_Ci in a new species different from the traditional zinc oxide powder, which is different from the traditional crystalline zinc oxide, that is, SNS_Ci@ZnO with excellent sunscreen properties is prepared, which corresponds to the FT-IR pattern.

[0143] Depend on Figure 5 The TEM image of the sunscreen material SNS_Ci@ZnO shows that the microsphere surface of the sunscreen material SNS_Ci@ZnO has an obvious small signal peak, which indicates that zinc oxide is successfully loaded on the surface of the silica microsphere SNS_Ci. Combined with the XRD spectrum analysis, no signal corresponding to the traditional crystalline zinc oxide was observed. It can be inferred that when the appropriate amount of zinc salt is added during synthesis, secondary deposition occurs on the surface of the silicon microsphere to generate zinc oxide, which is mainly loaded on the surface of the silica microsphere (SNS_Ci) in a different way from the traditional crystalline zinc oxide, that is, SNS_Ci@ZnO with excellent sunscreen properties is prepared.

[0144] Figure 6 UV spectra of pure zinc oxide ZnO, silica microspheres SNS-Ci and sunscreen material SNS-Ci@ZnO; Generally speaking, when the absorbance value of a sample in the UVB band is at least higher than 1.0 and the absorbance value in the UVA band is at least higher than 0.5, the sample can be considered to have sunscreen performance. Figure 6 It can be seen that in a 1wt% glacial acetic acid solution containing 0.5wt% chitosan, when the concentration of the sunscreen material SNS_Ci@ZnO is 1mg / mL, the absorbance value is the largest, and its sunscreen performance is better than that of traditional zinc oxide at this concentration, and is significantly better than that of the simple silica microspheres SNS_Ci prepared by the present invention.

[0145] Depend on Figure 7From the UV spectra of the sunscreen material SNS_Ci@ZnO with different zinc acetate addition amounts (addition amount is 0.05~1.0mL), it can be seen that when the sunscreen material SNS_Ci@ZnO with different zinc oxide loading amounts is dispersed in a 1wt% glacial acetic acid solution containing 0.5wt% chitosan, and the sample concentration is controlled to be 1.0mg / mL, the sunscreen material SNS_Ci@ZnO-1 (i.e., SNS_Ci@ZnO-1 in Example 7) with an addition amount of 0.2mL of zinc acetate solution has the largest absorbance value, indicating that its sunscreen performance is the best. This is mainly because (1) when the amount of zinc salt is relatively small during synthesis, that is, when the amount of zinc acetate added is different from 0.05 to 0.2 mL (the concentration of zinc acetate solution is 5 mmol / L), based on the interaction between zinc ions and negative ions on the surface of silicon microspheres, zinc ions are alkaline hydrolyzed and loaded on the surface of silicon microspheres in the form of a new phase (as shown in the XRD diagram, there is no characteristic crystalline diffraction peak corresponding to crystalline zinc oxide in the sunscreen material SNS_Ci@ZnO), and it exists in a non-crystalline form. Therefore, it will show better skin feel and sunscreen performance than pure zinc oxide; (2) when the amount of zinc salt increases during synthesis, that is, when it is greater than 0.2 mL, the amount of zinc oxide loaded on the surface of silicon microspheres increases, and the crystalline phase of crystalline zinc oxide will be generated, which will not only cause the product's sunscreen performance to gradually decrease, but also significantly deteriorate the skin feel (skin feel astringent), similar to pure zinc oxide. Therefore, when the amount of zinc acetate solution is controlled within a certain range during synthesis, the sunscreen performance of the new sunscreen material SNS_Ci@ZnO is significantly better than that of pure zinc oxide.

[0146] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A zinc oxide sunscreen material based on monodisperse silicon microspheres, characterized in that: The zinc oxide sunscreen material based on monodisperse silicon microsphere modification comprises silicon dioxide microspheres and zinc oxide loaded on the surface of the silicon dioxide microspheres, and the preparation method comprises: S1. Provide silica microspheres with negatively charged active groups carboxyl distributed on the surface, specifically S1.1 provides a solution C containing citric acid: S1.1.1 Dissolve citric acid in anhydrous ethanol, stir to fully dissolve it, and obtain solution A; S1.1.2 Dilute solution A with an appropriate amount of pure water to obtain solution B; S1.1.3 Dissolve ammonia water in solution B, stir to fully dissolve it, and obtain solution C containing citric acid; the amount of citric acid added in the solution A is 0.1~0.5g, and the amount of anhydrous ethanol added is 100mL; the amount of pure water added in the solution B is 30mL; the concentration of ammonia water in the solution C containing citric acid is 25wt%, and the amount added is 2~15mL; S1.2 Provide ethyl orthosilicate solution D: S1.2.1 Dissolve tetraethyl orthosilicate in anhydrous ethanol and fully dissolve by ultrasonication to obtain a tetraethyl orthosilicate solution D; the amount of tetraethyl orthosilicate added in the tetraethyl orthosilicate solution D is 4-15 mL, and the amount of anhydrous ethanol added is 10-30 mL; S1.3 adding tetraethyl orthosilicate solution D dropwise into solution C containing citric acid, fully reacting to obtain suspension E, filtering and washing to obtain silica microspheres with negatively charged active groups carboxyl distributed on the surface; the full reaction time in step S1.3 is 8 to 12 hours; washing with pure water and anhydrous ethanol in sequence in step S1.3; S2. In an alkaline environment, positively charged zinc ions are deposited on the surface of the silica microspheres in step S1 to form zinc hydroxide, thereby obtaining silica microspheres loaded with zinc hydroxide; and a zinc oxide sunscreen material based on monodisperse silica microspheres is obtained by heat treatment, specifically, S2.1, zinc acetate solution is added dropwise to the silica microsphere suspension G, and the suspension H is obtained by sufficient reaction: S2.1.1 Disperse the silica microspheres prepared in step S1 in anhydrous ethanol to obtain a suspension F; S2.1.2 Dissolve ammonia water in the suspension F to obtain a silica microsphere suspension G; In the step S2.1.1, the amount of silica microspheres added is 5 g, and the amount of anhydrous ethanol added is 40 mL; in the step S2.1.2, the concentration of ammonia water is 25 wt %, and the amount added is 1 mL; The concentration of the zinc acetate solution is 5 mmol / L, and the addition amount is 0.1-0.2 mL or 0.4 mL; S2.2 adding sodium hydroxide solution dropwise to suspension H to fully react to obtain suspension I; the concentration of sodium hydroxide solution in step S2.2 is 1 mmol / L, and the amount added is 1 mL; S2.3 Filter the suspension I, wash it, dry it and calcine it to obtain a zinc oxide sunscreen material modified with monodisperse silicon microspheres: S2.3.1 Filter the suspension I, wash it with pure water and anhydrous ethanol in turn and dry it to obtain powder J; the drying temperature in the step S2.3.1 is 55°C.

2. The zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 1, characterized in that: The mass ratio of the silica microspheres to the zinc oxide loaded on the surface of the silica microspheres is 400-600; and the polymer dispersibility index (PDI) of the silica microspheres loaded with zinc hydroxide is 0.069-0.

181.

3. The zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 1, characterized in that: The particle size range of the zinc oxide sunscreen material based on the modification of monodisperse silicon microspheres is 1220-1300 nm; and the potential range of the zinc oxide sunscreen material based on the modification of monodisperse silicon microspheres is -42.6--41.2 mV.

4. A method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to any one of claims 1 to 3, characterized in that: The steps include: S1. providing silica microspheres having negatively charged active groups carboxyl groups distributed on the surface; S2. In an alkaline environment, positively charged zinc ions are deposited on the surface of the silica microspheres in step S1 to form zinc hydroxide, and a zinc oxide sunscreen material modified based on monodisperse silica microspheres is obtained by heat treatment.

5. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 4, characterized in that: The step S1 comprises: S1.1 provides a solution C containing citric acid; S1.2 provides a ethyl orthosilicate solution D; S1.3 Add tetraethyl orthosilicate solution D dropwise into solution C containing citric acid to fully react to obtain suspension E. After suction filtration and washing, silica microspheres with negatively charged active groups carboxyl distributed on the surface are obtained.

6. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 5, characterized in that: The step S1.1 comprises: S1.1.1 Dissolve citric acid in anhydrous ethanol and stir to fully dissolve it to obtain solution A; S1.1.2 Dilute solution A with an appropriate amount of pure water to obtain solution B; S1.1.3 Dissolve ammonia water in solution B and stir to fully dissolve it to obtain solution C containing citric acid; The amount of citric acid added to the solution A is 0.1-0.5 g, and the amount of anhydrous ethanol added is 100 mL; The amount of pure water added to the solution B is 30 mL; The concentration of ammonia water in the citric acid-containing solution C is 25wt%, and the addition amount is 2-15mL; The step S1.2 comprises: S1.2.1 Dissolve tetraethyl orthosilicate in anhydrous ethanol and fully dissolve it by ultrasonication to obtain tetraethyl orthosilicate solution D; the amount of tetraethyl orthosilicate added in the tetraethyl orthosilicate solution D is 4-15 mL, and the amount of anhydrous ethanol added is 10-30 mL.

7. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 5, characterized in that: The sufficient reaction time in step S1.3 is 8 to 12 hours; In the step S1.3, the sample is washed with pure water and anhydrous ethanol in sequence.

8. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 4, characterized in that: The step S2 comprises: S2.1 Add zinc acetate solution dropwise into silica microsphere suspension G to fully react to obtain suspension H; S2.2 Add sodium hydroxide solution dropwise into suspension H to fully react to obtain suspension I; S2.3 The suspension I is filtered, washed, dried and calcined to obtain a zinc oxide sunscreen material modified with monodisperse silicon microspheres.

9. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 8, characterized in that: The step S2.1 comprises: S2.1.1 Disperse the silica microspheres prepared in step S1 in anhydrous ethanol to obtain a suspension F; S2.1.2 dissolving ammonia water in suspension F to obtain silica microsphere suspension G; In the step S2.1.1, the amount of silica microspheres added is 5 g, and the amount of anhydrous ethanol added is 40 mL; in the step S2.1.2, the concentration of ammonia water is 25 wt %, and the amount added is 1 mL; The concentration of the zinc acetate solution is 5 mmol / L, and the addition amount is 0.1-0.2 mL or 0.4 mL; The concentration of the sodium hydroxide solution in step S2.2 is 1 mmol / L, and the amount added is 1 mL; The step S2.3 comprises: S2.3.1 Filter the suspension I, wash it with pure water and anhydrous ethanol in turn, and dry it to obtain powder J; The drying temperature in step S2.3.1 is 55°C.

10. The method for preparing a zinc oxide sunscreen material based on monodisperse silicon microspheres modified according to claim 8, characterized in that: The reaction time of step S2.1 is 0.5 to 1.5 hours; The reaction time of step S2.2 is 0.5-1.0h; The calcination temperature in step S2.3 is 200° C. and the calcination time is 2 h.

Citation Information

Patent Citations

  • Inorganic-organic sun-screening agent composite microsphere and preparation method thereof

    CN109771306A

  • Selective composite microsphere adsorption material as well as preparation method and application thereof

    CN113877549A